Graphics processing unit computing and exploitation of hardware accelerators. (2nd January 2013) - Amor, Margarita; Doallo, Ramón; Fraguela, Basilio B.; Herrero, José R.; Quintana‐Ortí, Enrique S.; Strzodka, Robert; Hidalgo, Jose Ignacio; Fernández‐de‐Vega, Francisco; Amor, Margarita; Doallo, Ramón; Fraguela, Basilio B.; Herrero, José R.; et al.
SUMMARY This special issue contributes to this promising field with extended and carefully reviewed versions of selected papers from two workshops, namely the 2nd Minisymposium on GPU Computing, which was held as part of the 9th International Conference on Parallel Processing and Applied Mathematics (PPAM 2011) in Torun (Poland); and the Workshop on Exploitation of Hardware Accelerators (WEHA 2011), which was held in conjunction with The 2011 International Conference on High Performance Computing & Simulation in Istanbul (Turkey). Copyright © 2012 John Wiley & Sons, Ltd.